2019
DOI: 10.1177/0961203319862610
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNFSF4 rs1234315, rs2205960 polymorphisms and systemic lupus erythematosus susceptibility: a meta-analysis

Abstract: Background The aim of this study was to explore the association between tumor necrosis factor superfamily number 4 (TNFSF4) rs1234315, rs2205960 polymorphisms and systemic lupus erythematosus (SLE) susceptibility. Methods A meta-analysis was performed on the association between rs1234315 and rs2205960 polymorphisms and SLE by allelic contrast, additive model, recessive model and dominant model. Results Regarding rs1234315 polymorphism, a total of five studies were included (6575 cases, 14,798 controls). Meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These differences reflect the genetic heterogeneity of SLE among the world populations [10]. Another meta-analysis was carried out by Wang et al (2019) and Lee et al (2012) stated similar results, which found a significant association between the T allele of rs2205960 and SLE in all European and Asian subjects. A significant association was also found in the TT genotype with SLE in the same study [12,21].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These differences reflect the genetic heterogeneity of SLE among the world populations [10]. Another meta-analysis was carried out by Wang et al (2019) and Lee et al (2012) stated similar results, which found a significant association between the T allele of rs2205960 and SLE in all European and Asian subjects. A significant association was also found in the TT genotype with SLE in the same study [12,21].…”
Section: Discussionmentioning
confidence: 69%
“…SNP rs2205960 (G>T) causes an increase in OX40L expression, which influences the development of SLE disease. Overexpression of OX40L may increase the stimulation of CD4 + T helper effector cells and increase the response of follicular T helper cells whose function is to help B cells proliferate and form antibodies causing inflammation and autoimmunity in specific organs [11][12][13]. The OX40L signaling suppresses the generation and function of interleukin-10 (IL10)-producing CD4 + type 1 regulatory T cells, which play an important role in maintaining peripheral resistance [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, renal damage was uncommon in our cohort [6.9%], in contrast to most other studies (14–32.4%) [ 7 , 28 , 29 , 31 , 32 , 33 ], which may be because the expression of renal disease is more aggressive in some ethnic groups (11). Although renal damage was infrequent, it was significantly associated with rs2205960 of TNFSF4 gene, which was previously associated with SLE susceptibility and lupus nephritis (LN) [ 17 , 30 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TNFSF4 molecule is a type II transmembrane protein, which is mainly expressed on several activated immune cells. It plays an important role in effector T-cell survival, B-cell differentiation and proliferation, cytokine production and memory cell formation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%